Large Rapidity Gap Method to Select Soft Diffraction Dissociation at the LHC - Emily Nurse; Sercan Sen (Advances in High Energy Physics)
In proton-proton (pp) collisions, any process involves exchanging the vacuum quantum numbers is known as diffractive process. A diffractive process with no large Q2 is called soft diffractive process. The diffractive processes are important for understanding nonperturbative QCD effects and they also constitute a significant fraction of the total pp cross section. The diffractive events are typically characterized by a region of the detector without particles, known as a rapidity gap. In order to observe diffractive events in this way, we consider the pseudorapidity acceptance in the forward region of the ATLAS and CMS detectors at the Large Hadron Collider (LHC) and discuss the methods to select soft diffractive dissociation for pp collisions at s=7 TeV. It is shown that, in the limited detector rapidity acceptance, it is possible to select diffractive dissociation events by requiring a rapidity gap in the event; however, without using forward detectors, it seems not possible to fully separate single and double diffractive dissociation events. The Zero Degree Calorimeters can be used to distinguish the type of the diffractive processes up to a certain extent.